THE INNER JOURNEY OF DENIAS TO GET EDUCATION IN DENIAS, SENANDUNG DI ATAS AWAN - Jermi A. Pello; Meilinda Meilinda (Kata Kita: Journal of Language, Literature, and Teaching, 2015)
The first education themed Indonesian movie during Indonesian film industry history is exposed in, Denias, Senandung di Atas Awan. This film presents a struggle of a boy, Denias,  in pursuing his dream to achieve a better education and through this movie he is also recognized as a hero. Moreover, in order to help my pursuit in answering my statement of the problem, I applied Christopher Vogler’s theory which is the Character Arc. Thus, in the end of this study, I can conclude that a common boy can also be recognized as a hero because  he has a great effort. This effort can be seen through his (Denias’) inner journey that leads him to be an educated person.